Sustainable Rural Livelihoods of Communities Surrounding Tempe Lake - Amandaria, Riri; Mario, Mario; Wahda, Muhammad Aksha (Universitas Negeri Makassar, 2024)
This study investigates the complex challenges faced by communities surrounding Tempe Lake, primarily driven by environmental, socio-economic, and institutional factors that threaten their livelihoods. The recurrent flooding, occurring twice a year, disrupts agricultural production and fishing activities, while the degradation of natural resources due to overfishing, pollution, and deforestation further exacerbates vulnerabilities. The primary objective of this research is to identify and examine the livelihood resources available to these communities, focusing on their natural, human, financial, social, and physical assets. A descriptive qualitative approach was employed, utilizing in-depth interviews, observations, and literature reviews to gather comprehensive data on the community's livelihood strategies and challenges. The findings reveal that the residents of Tempe Lake exhibit remarkable resilience, relying on a combination of traditional knowledge and adaptive practices to navigate their environmental challenges. The study highlights the importance of social networks and trust within the community, which facilitate collaboration and mutual support during crises. Additionally, it underscores the critical role of the lake's resources in sustaining both economic stability and cultural identity. However, the research also identifies significant gaps in education and access to financial services, which limit the community's ability to diversify their livelihoods and improve their overall well-being. The results emphasize the need for targeted interventions, including financial literacy programs, sustainable resource management practices, and disaster preparedness training, to enhance the resilience of the Tempe Lake communities. Ultimately, this study contributes to a deeper understanding of the interplay between livelihoods and environmental sustainability, offering valuable insights for policymakers and stakeholders aiming to support these vulnerable populations.